2020
DOI: 10.1136/bmjdrc-2020-001508
|View full text |Cite
|
Sign up to set email alerts
|

Islet inflammation is associated with pancreatic fatty infiltration and hyperglycemia in type 2 diabetes

Abstract: IntroductionChronic inflammation is observed in type 2 diabetes islets, and fat deposition in the pancreas affects insulin secretion and glucose tolerance. However, the relationship between this inflammation and pancreatic fat deposition has not been elucidated.Research design and methodsWe examined pancreatic sections from 60 Japanese patients obtained by pancreatectomy. We evaluated pancreatic fat-cell area (%) and CD68-positive (CD68+) cells per islet histologically and examined the relationships between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…The results in humans regarding the relationship between pancreatic fat and glucose metabolism are inconsistent [ 74 ]. We have reported that there is no significant difference in the intrapancreatic fat area between subjects with and without diabetes in a histological analysis [ 90 ], which is consistent with other histological studies [ 65 , 91 ]. On the other hand, several reports have shown that pancreatic fat increased with the progression of glucose intolerance or T2DM [ 92 , 93 , 94 ].…”
Section: Beta Cell Mass In Obesity and Type 2 Diabetessupporting
confidence: 89%
“…The results in humans regarding the relationship between pancreatic fat and glucose metabolism are inconsistent [ 74 ]. We have reported that there is no significant difference in the intrapancreatic fat area between subjects with and without diabetes in a histological analysis [ 90 ], which is consistent with other histological studies [ 65 , 91 ]. On the other hand, several reports have shown that pancreatic fat increased with the progression of glucose intolerance or T2DM [ 92 , 93 , 94 ].…”
Section: Beta Cell Mass In Obesity and Type 2 Diabetessupporting
confidence: 89%
“…We investigated pancreatic fat-cell infiltration in nondiabetic patients undergoing pancreatectomy. We found that fat-cell infiltration was associated with postoperative deterioration of glucose tolerance [ 19 ], and that this infiltration in addition to hyperglycemia was also associated with islet inflammation, which was evaluated by macrophage infiltration around or within islets [ 20 ]. Furthermore, it has been clarified that pancreatic fat evaluated by computed tomography value is involved in the decrease in endogenous insulin-secreting capacity in type 2 diabetic patients [ 21 ].…”
Section: Ectopic Fat In Pancreasmentioning
confidence: 99%
“…Analysis of histological pancreatic sections has shown high numbers of macrophage marker CD68+ cells in the vicinity of islets derived from individuals with diabetes. Noteworthy, in other studies, the presence of these cells in islets was positively correlated with the occurrence of amyloid structures and fibrosis [26,35] as well as increased body mass index, fasting C-peptide immunoreactivity, fat cell area, and hyperglycemia [36]. In the reported amyloid-positive cases, CD68 + cells predominated over tissue repair-oriented macrophages (double-positive for CD163 and CD204 markers) [35].…”
Section: Chronic Inflammation and Diabetesmentioning
confidence: 75%